Probing Crowdedness of Artificial Organelles by Clustering Polymersomes for Spatially Controlled and pH-Triggered Enzymatic Reactions - Wang, Peng; Moreno, Silvia; Janke, Andreas; Boye, Susanne; Wang, Dishi; Schwarz, Simona; Voit, Brigitte; Appelhans, Dietmar (Biomacromolecules, 2022)
Most sophisticated biological functions and features of cells are based on self-organization, and the coordination and connection between their cell organelles determines their key functions. Therefore, spatially ordered and controllable self-assembly of polymersomes to construct clusters to simulate complex intracellular biological functions has attracted widespread attention. Here, we present a simple one-step copper-free click strategy to cross-link nanoscale pH-responsive and photo-cross-linked polymersomes (less than 100 nm) to micron-level clusters (more than 90% in 0.5-2 μm range). Various influencing factors in the clustering process and subsequent purification methods were studied to obtain optimal clustered polymeric vesicles. Even when polymeric vesicles separately loaded with different enzymes (glucose oxidase and myoglobin) are coclustered, the overall permeability of the clusters can still be regulated through tuning the pH values on demand. Compared with simple blending of those enzyme-loaded polymersomes, the rate of enzymatic cascade reaction increased significantly due to the interconnected complex microstructure established. The connection of catalytic nanocompartments into clusters confining different enzymes of a cascade reaction provides an excellent platform for the development of artificial systems mimicking natural organelles or cells.
CRIS-Team Scopus Importer:2023-03-20